Dynamic Technical and Environmental Efficiency Performance of Large Gold Mines in Developing Countries - Isaiah Hubert Magambo; Johane Dikgang; Dambala Gelo; Fiona Tregenna (ZBW – Leibniz Information Centre for Economics, 2021)
This study used the by-production model specification to separate emission-generating technologies from `desirable outputs' technology. It then employed the dynamic efficiency model, following the Dynamic Directional Input Distance Function specifications to compute the deterministic, dynamic environmental and technical efficiencies of large gold mines in developing countries. Using firm-level data from 2009 to 2018, the study found that on average, dynamic technical efficiency in these mines was 73%; the average dynamic technical efficiency was observed to have a decreasing trend, of 0.3% annually. The study also found that on average, dynamic environmental efficiency was 56%. However, the average dynamic environmental efficiency trend had a decrease of 0.6% annually. The poor performance and downward trends could be attributed partly to downward investment trends over time, and the increasing complexity of extracting gold deposits from low-grade ore, as well as to prices. They could also be the result either of poor institutional capacity, as far as environmental policies, regulations, and enforcement are concerned; or of supply-side structural rigidity – in particular, low-capacity, and unreliable energy supply, mostly from bad inputs such as coal and heavy fuels or both, which calls for the use of alternative energy sources.
Keywords: D24; D25; Q55; Q58; 330; environmental efficiency; gold mines; technical efficiency; undesirable output